Characteristics of Isothermic Sorption Curves and Determination of the Best Equation Model for Egg Flour - Syamsuri, Riswita; Dirpan, Andi; Laga, Amran; Salengke, Salengke (Department of Technology of Agricultural product (THP) Jambi University, 2024)
Egg flour storage is influenced by temperature, relative humidity, and water activity. Equilibrium of moisture content is closely related to sorption isotherm to determine optimal storage conditions. This research evaluated the characteristics of isothermic sorption curves and determined the appropriate equation model to describe isothermic sorption curves on various types of egg flour. The egg flour used is egg white flour, egg yolk flour, and whole egg flour (white and yolk), which is ohmic pasteurized for 5 minutes at 600C, then oven and vacuum dried. After that, the samples were stored in a desiccator with different humidity levels (10-80%) at a temperature of 300C. The desiccator is inserted into the incubator to maintain the temperature. This research used four equation models: Oswin, Chung-Pfost, Caurie, and Helsey. The results showed that the isothermic sorption curve of egg flour had a sigmoid absorption type, which reflected a Type II isothermic pattern. Based on the coefficient of determination (R2) and RMSE, the Oswin equation model is the most appropriate for describing the isothermic sorption pattern for all egg flour tested. This model can be used to predict optimal storage conditions for egg flour.